Pemberdayaan Urban Farming melalui Desain Kemasan Produk Berbasis Digital Canva di Kelurahan Kalisegoro - Widowati, Fika Ulfa (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
Urban agriculture in urban areas requires digital downstreaming to increase the economic value of products. This study aims to empower the community of Kalisegoro Village through the integration of digital technology in agricultural innovation. Using a theoretical framework of digital-based community empowerment, the implementation methods include socialization, digital literacy, and packaging design workshops using the Canva platform. Involving 14 KKN students and 50 residents, the results of the activity showed a significant increase in technical cultivation skills and visual branding abilities. The use of Canva has been proven to democratize access to professional design, thereby increasing the competitiveness and selling value of local products through representative packaging. In conclusion, the synergy of digital technology and urban farming effectively encourages the transformation of local agricultural products into high-value commodities in the digital era.